2018
DOI: 10.3390/agronomy8100218
|View full text |Cite
|
Sign up to set email alerts
|

Tipburn Severity and Calcium Distribution in Lisianthus (Eustoma Grandiflorum (Raf.) Shinn.) Cultivars under Different Relative Air Humidity Conditions

Abstract: Tipburn is a major problem for the production of lisianthus (Eustoma grandiflorum (Raf.) Shinn.) cultivars. Relative air humidity is regarded as a key environmental factor affecting tipburn severity in commercial crops. However, there are limited studies comparing the occurrence of tipburn and calcium (Ca) distribution in lisianthus cultivars under different relative air humidity conditions. Accordingly, we investigated the effect of relative air humidity on tipburn severity, transpiration rate, and Ca content… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 14 publications
0
18
0
2
Order By: Relevance
“…, Tokyo, Japan): 0.4 mL/L) and its nutrient concentrations were same as that used in previous studies [17,18,26]. Five weeks after transfer to the phytotron, plugs were transplanted into 0.25 L polyethylene pots filled with Metro Mix 350.…”
Section: Plantsmentioning
confidence: 99%
See 1 more Smart Citation
“…, Tokyo, Japan): 0.4 mL/L) and its nutrient concentrations were same as that used in previous studies [17,18,26]. Five weeks after transfer to the phytotron, plugs were transplanted into 0.25 L polyethylene pots filled with Metro Mix 350.…”
Section: Plantsmentioning
confidence: 99%
“…Whole leaves were scored using an arbitrary tipburn severity index with ranking from 0 to 1 (0, asymptomatic; 0.2, deformed leaf margins; 0.5, leaf-tip chlorosis; 1, leaf-tip necrosis) [26]. The severity of tipburn in each plant was defined as Tipburn severity = {(severity index × leaf number)/whole leaves number per pot} × 100…”
Section: Tipburn Severity and Incidencementioning
confidence: 99%
“…In rice [16] and barley [17], it has been reported that a high K concentration inhibits Ca uptake. Therefore, a high content ratio of K in the nutrient solution in our previous experiments [10][11][12][13] may have prevented Ca acquisition and distribution in some lisianthus cultivars. It is necessary to investigate the relevance of Ca and K concentrations in lisianthus cultivars.…”
Section: Introductionmentioning
confidence: 86%
“…These cultivars were selected based on the results for tipburn severity (as high, medium, or low damage) reported previously [10]. Seedlings were developed and raised as previously reported [10][11][12][13].…”
Section: Plant Materialsmentioning
confidence: 99%
See 1 more Smart Citation